Pengaruh Program Market Day Terhadap Kemampuan Literasi Keuangan Anak Usia 5-6 Tahun di RA Sunan Muria Poncokusumo-Malang - Sa’adatul Kholidiyah; Ardhana Reswari (Universitas Islam Lamongan, 2024)
Early financial literacy education is crucial for preparing children to face future financial challenges. This study aims to measure the impact of the Market Day program on the financial literacy of 5-6-year-old children at RA Sunan Muria Poncokusumo, Malang. The research uses a quantitative experimental approach with a one group pretest-posttest design. The results indicate a significant improvement in children's financial literacy after participating in the Market Day program, with a paired sample test significance value of 0.000 < 0.05. The Market Day program has proven effective in enhancing children's understanding of financial concepts, money management, and financial transactions. The study concludes that the Market Day program can be a valuable alternative for developing early childhood financial literacy.